2010
DOI: 10.1519/jsc.0b013e3181bdddda
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Resistance Training on Strength and Power in Upper Extremities in Wheelchair Athletes

Abstract: Little is known about strength training in subjects with spinal cord injury (SCI), especially in athletes performing competitive sports. Sixteen male subjects participated in this study-8 with SCI and 8 healthy physical education students (control subjects). The 8-week program consisted of heavy-resistance exercise performed twice per week with 10 to 12 repetitions in 5 sets. Subjects' performances were tested in static and in dynamic conditions concerning several strength and power parameters. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 20 publications
3
62
0
6
Order By: Relevance
“…These findings correspond with other studies that have found simultaneous improvements of maximal strength and sprint abilities following training programs including exercises such as bench press and dumbbell bench pull in kayaking (Liow & Hopkins, 2003) and in wheelchair racing (Turbanski & Schmidtbleicher, 2010). The present improvements in 1RM are slightly lower than the 10% increase in 1RM in a double poling exercise after 12 weeks of heavy strength training in highly trained cross-country skiers (Losnegard et al, 2011), and much lower than the 19-23% improvement after 9-12 weeks heavy strength training in cross country skiers and nordic combined athletes (Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings correspond with other studies that have found simultaneous improvements of maximal strength and sprint abilities following training programs including exercises such as bench press and dumbbell bench pull in kayaking (Liow & Hopkins, 2003) and in wheelchair racing (Turbanski & Schmidtbleicher, 2010). The present improvements in 1RM are slightly lower than the 10% increase in 1RM in a double poling exercise after 12 weeks of heavy strength training in highly trained cross-country skiers (Losnegard et al, 2011), and much lower than the 19-23% improvement after 9-12 weeks heavy strength training in cross country skiers and nordic combined athletes (Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Associations between upper-body strength and various types of performances are further supported by studies on elite kayakers (Liow & Hopkins, 2003;Uali et al, 2012), wheelchair racers (Turbanski & Schmidtbleicher, 2010), surfers (Sheppard et al, 2012) and luge athletes (Crossland, Hartman, Kilgore, Hartman, & Kaus, 2011;Platzer, Raschner, & Patterson, 2009). A few of these studies also showed simultaneous improvements of maximal strength and sprint abilities with heavy upper-body strength training (Liow & Hopkins, 2003;Turbanski & Schmidtbleicher, 2010), whereas such training in cross-country skiers improved upper-body strength, skiing economy and endurance performance (Hoff, Gran, & Helgerud, 2002;Losnegard et al, 2011;Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012). Whether these strength training effects apply for elite athletes who are specialized in an isolated upper-body movement needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 79%
“…arm ergometry, resistance training, and use of mobile arm supports) improve the overall performance of functional daily activities and quality of movement in patients with and without SCI. [25][26][27][28][29][30][31] Neuromuscular re-education and manual resistance techniques also facilitate achieving an optimal level of motor recovery prior to introducing adaptations and assistive technology. These findings seem to support the concept that focusing on strengthening activities in OT is an important step in achieving functional tasks.…”
Section: 24mentioning
confidence: 99%
“…Results indicated that athletes using wheelchairs showed a significantly higher improvement in the force development rate. 8 Another study found that athletes with quadriplegia who used wheelchairs playing rugby had better respiratory muscle strength and thoracic mobility than those sedentary subjects with quadriplegia. 9 Wheelchair rugby training has also been proven to be effective in increasing forced vital capacity, forced expired volume after 1 s, and maximal voluntary ventilation values for people with tetraplegia.…”
Section: Introductionmentioning
confidence: 99%